Implementation of KM strategies in the Malaysian telecommunication industry: An empirical analysis - Chong, Chin Wei; Chong, Siong Choy; Wong, Kuan Yew (Emerald Group Publishing Limited, 2007)
Purpose - This purpose of this paper is to assess the perceived importance and actual implementation of four knowledge management (KM) strategies, i.e. culture; leadership; information technology; and measurement, in the Malaysian telecommunication industry. Design/methodology/approach - Data were collected from 289 telecommunication organizations in Malaysia and analyzed using indices and parametric statistics. Findings - The paired t-test results show significant differences among all the KM strategies in terms of their importance and actual implementation. Strategies such as technology, culture and leadership are moderately implemented, with measurement being the least implemented factor. Research limitations/implications - This paper focuses on KM implementation rather than on learning and knowledge utilization. Practical implications - Malaysian telecommunication organizations should give equal attention to the implementation of all the four KM strategies. They need to have proper planning and overcome any problem or difficulty for the four KM strategies to be implemented smoothly, and subsequently narrow the gaps between the perceived importance and actual implementation of these strategies. Such viable practice will significantly help the government of Malaysia to achieve the K-Economy status and Vision 2020. Originality/value - This study is perhaps one of the first to empirically investigate and compare the perceived importance and actual implementation of the four KM strategies in the Malaysian telecommunication industry.